Toxicological impact of three pharmacological therapeutics on human sperm - Garcia, Carolina Capucha (2022)
Therapeutic drugs can negatively affect male fertility by inducing toxic effects that impair sperm production and/or function. Some drugs are able to cross the blood-testis barrier (BTB) and act directly on germ cells, interfering with sperm function. With the world pandemic of COVID-19, several drugs were repurposed as treatment options. As a result, these drugs started to be extensively administered worldwide. The urge for full knowledge on drugs’ safety became even more evident, to avoid undesirable side effects. Therefore, the aim of this in vitro study was to evaluate the toxicological effects of three therapeutic drugs used in COVID-19, in human sperm cells. Hydroxychloroquine (HCQ; antimalarial), dexamethasone (DEX; glucocorticoid) and remdesivir (RDV; antiviral) were the drugs studied. DEX and RDV are also recommend in co-administration for some COVID-19 patients, thus, these two drugs were evaluated for individual combined effects. Sperm vitality and motility, sperm oxidative stress and DNA damages were assessed in sperm cells exposed to usual therapeutic regimen of each drug and compared to a control group. HCQ was the only drug to induce significant effects in sperm vitality and motility. All drugs induced sperm DNA fragmentation, without alter the oxidative stress levels. Therefore, this study suggests HCQ is the most toxic drug for sperm cells, and that sperm DNA fragmentation is induced by different mechanism rather than exclusively due to oxidative stress. Moreover, results outlined the importance to include sperm DNA fragmentation evaluation in routine sperm analysis at fertility clinics. DEX and RDV seem to have addictive effects when administered simultaneously, however, further investigation is required to confirm these effects.